Inflammasome Signaling and Bacterial Infections - Backert, Steffen (Current Topics in Microbiology and Immunology, 2016)
This volume details our current understanding of the architecture and signaling capabilities of known canonical and non-canonical inflammasome complexes and highlights their action, in particular in response to infection with important bacterial model organisms and the corresponding disease pathologies. The first chapters review new insights into the assembly and structures of inflammasome components and emphasize general strategies of up- and downstream signaling events. In addition, the authors specifically discuss the composition and activity of inflammasomes during infection with various gut pathogens (Salmonella, Shigella, Yersinia, Listeria and Helicobacter), respiratory pathogens (Mycobacterium, Legionella, Burkholderia and Streptococcus) as well as skin and soft tissue pathogens (Francisella and Staphylococcus). The discoveries presented provide a better understanding of the cellular and molecular biology of inflammasomes, which will pinpoint important new therapeutic targets for the treatment and prevention of multiple infectious diseases in the future. It is a valuable resource for students, scientists and clinicians, providing up-to-date information on this emerging research topic.